2016
DOI: 10.3389/fpls.2016.00790
|View full text |Cite
|
Sign up to set email alerts
|

Quinoa Seed Quality Response to Sodium Chloride and Sodium Sulfate Salinity

Abstract: Quinoa (Chenopodium quinoa Willd.) is an Andean crop with an edible seed that both contains high protein content and provides high quality protein with a balanced amino acid profile in embryonic tissues. Quinoa is a halophyte adapted to harsh environments with highly saline soil. In this study, four quinoa varieties were grown under six salinity treatments and two levels of fertilization, and then evaluated for quinoa seed quality characteristics, including protein content, seed hardness, and seed density. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 25 publications
2
25
0
2
Order By: Relevance
“…In the present study, soil salinity did not significantly influence on protein content of Peruvian cultivar Hualhuas. Similar trend obtained by Wu et al (2016) who reported that increasing NaCl concentrations up to 32 dSm -1 did not alter protein content in quinoa seeds. In this regard, mentioned that the lower C/N ratio at high saline levels (>300 mM NaCl) was a reasonable explanation of an increase in protein content, accompanied with a reduction in total carbohydrate.…”
Section: Discussionsupporting
confidence: 75%
“…In the present study, soil salinity did not significantly influence on protein content of Peruvian cultivar Hualhuas. Similar trend obtained by Wu et al (2016) who reported that increasing NaCl concentrations up to 32 dSm -1 did not alter protein content in quinoa seeds. In this regard, mentioned that the lower C/N ratio at high saline levels (>300 mM NaCl) was a reasonable explanation of an increase in protein content, accompanied with a reduction in total carbohydrate.…”
Section: Discussionsupporting
confidence: 75%
“…From an economic point of view, ancient grains are low‐input crops with lower needs in fertilizers and they might be a suitable crop in lower‐income countries. Quinoa, for example, is known for its tolerance to soil salinity indicating its suitability to harsh conditions (Wu and others ).…”
Section: Ancient Grains‐based Foodstuffs: Nutritional Added Value Andmentioning
confidence: 99%
“…is an ancient seed crop from the Andean region, and in the last 30 years, it has gained considerable attention worldwide due to its nutritional and health benefits, as well as its flavourful and high‐quality seeds (Aluwi, Murphy, & Ganjyal, ; Kowalski, Medina‐Meza, Thapa, Murphy, & Ganjyal, ; Wu, Morris, & Murphy, , ; Wu, Ross, Morris, & Murphy, ). Most notably, it is prized for its well‐balanced complement of amino acids and high mineral concentration of iron, calcium and phosphorus (González, Konishi, Bruno, Valoy, & Prado, ; Navruz‐Varli & Sanlier, ; Vega‐Gálvez et al., ; Wu, ; Wu, Peterson, Morris, & Murphy, ). In the last few years, quinoa production has been spreading around the world (Bazile, Jacobsen, & Verniau, ; Jacobsen, ).…”
Section: Introductionmentioning
confidence: 99%